2020
DOI: 10.1002/er.5295
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of germanium selenide electrodes for the integrated photo‐rechargeable battery

Abstract: Autonomous photo-rechargeable electronic energy storage device has become a new type of solution to the problems of renewable energy fluctuations and storage. The combination of light conversion equipment and energy storage equipment improves the packaging efficiency of the equipment, however how to explore a type of electrode materials for energy collection and storage become a real challenging issue. Here, we try to explore the GeSe nanoparticles as the potential idea electrode for the integrated photorechar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 37 publications
(41 reference statements)
0
11
0
Order By: Relevance
“…Despite these issues, several recent advances in this field suggest a promising future for photobatteries. In 2017, Paolella et al reported the photo-oxidation of LiFePO 4 nanocrystals under illumination in a two electrode battery system; however, the energy conversion efficiency was only 0.06–0.08% . GeSe nanoparticles have been reported as electrodes for a photorechargeable battery, showing a current increase of 8 μA·cm –2 under visible light illumination, although germanium may be very expensive for this application . Most recently, zinc-ion and lithium-ion batteries consisting of V 2 O 5 as the photocathode containing poly­(3-hexylthiophene-2,5-diyl) (P3HT) and reduced graphene oxide (rGO) which help in separation of photoinduced charges are reported with the first discharge efficiencies of 1.2% under 12 mW/cm 2 and 0.22% under 1 sun, for the zinc and lithium ion, respectively. , More materials suitable for high performance lithium-ion photobatteries (PHBATs) have yet to be identified, even though Li-ion is by far the most commonly used battery for cell phones, personal electronics, and transportation vehicles.…”
mentioning
confidence: 99%
“…Despite these issues, several recent advances in this field suggest a promising future for photobatteries. In 2017, Paolella et al reported the photo-oxidation of LiFePO 4 nanocrystals under illumination in a two electrode battery system; however, the energy conversion efficiency was only 0.06–0.08% . GeSe nanoparticles have been reported as electrodes for a photorechargeable battery, showing a current increase of 8 μA·cm –2 under visible light illumination, although germanium may be very expensive for this application . Most recently, zinc-ion and lithium-ion batteries consisting of V 2 O 5 as the photocathode containing poly­(3-hexylthiophene-2,5-diyl) (P3HT) and reduced graphene oxide (rGO) which help in separation of photoinduced charges are reported with the first discharge efficiencies of 1.2% under 12 mW/cm 2 and 0.22% under 1 sun, for the zinc and lithium ion, respectively. , More materials suitable for high performance lithium-ion photobatteries (PHBATs) have yet to be identified, even though Li-ion is by far the most commonly used battery for cell phones, personal electronics, and transportation vehicles.…”
mentioning
confidence: 99%
“…Recently, there have been some developments toward electrodes of batteries and capacitors that can directly harvest solar power without the need for solar cells, thereby offering an elegant solution for the challenges listed above. , Here, we present new light rechargeable electrochemical capacitors. In general, electrochemical supercacacitors have drawn attention in the scientific community because of their high power density, fast charge, long cycling life, and safe operation .…”
mentioning
confidence: 99%
“…Compared to classic systems where solar cells and batteries are separate devices, photo-batteries offer a more compact design without the need for external electronics to match the output of the energy solar cell to the battery. Therefore, a range of different materials have been considered for photo-batteries, including, for instance, halide perovskites, 2,3 organic molecules, 4 vanadium pentoxide, 5,6 germanium selenide, 7 and titanium dioxide. 8 Most photoelectrodes are fabricated by physically mixing of electrode materials with conductive additives, charge transfer materials and binders followed by casting on a collector electrode.…”
Section: Introductionmentioning
confidence: 99%